EQUIVOCO HISPANIMO: NOTAS SOBRE EL EXILIO REPUBLICANO Y PENSAMIENTO REACCIONARIO EN EL MEXICO DE LOS AÑOS 1940 (Res Publica. Revista de Historia de las Ideas Políticas, 2009)
This essay sustains an essential similarity between liberal Hispanism, as developed by post-Civil War exiles, and the theory of hispanidad elaborated by conservatives such as Maeztu, premised on the imperial presuppositions that seem to determine every relationship between Spain and Latin America.